HUBUNGAN PENGETAHUAN DAN MINAT IBU PASANGAN USIA SUBUR (PUS) DENGAN PENGGUNAAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) DI PUSKESMAS DURAI - Menda, Maria; Yunita, Prasida (Universitas Batam, 2019)
The data portrays Puskesmas Durai as the health centre with the lowest used of IUD for birth controlling in Karimun which reached only 12 people (1.1%) from the total population of 1.061 people. This study aims to investigate the correlation between knowledge and interest of childbearing age mothers toward IUD use in Puskesmas Durai in 2018. This study used analytical survey with control case study design. The sample of this study was 12 IUD users as the case group, meanwhile the control group was taken with a ratio of 1: 5, and thus 60 respondents were taken. Therefore the total sample was of 72 respondents. The data analysis technique employed was the Risk Estimate test. The result shows 15 people (20.8%) have good knowledge on IUD, however 57 of them (79.2%) have poor knowledge about IUD. On the other hand, it is also shown 15 people (20.8%) are interested in using IUS, but 57 of them (79.2%) have no interest at all. Based on the statistical test, it is indicated that there is no significant correlation between respondents’ knowledge and IUD use with Odds Ratio value of 0.723 (0.141-3.719). Besides, there is also no significant correlation between their interest and the use of IUD with Odds Ratio value of 0.723 (0.141-3.719). Therefore, it is concluded that the knowledge and interest of childbearing age mother are still low toward the IUD use for birth controlling tool, particularly in Puskesmas Durai in 2018. As the suggestion, it is hoped that health personnel to provide more information and health counseling specifically on the benefit of the UID as another contraception option.